Legal Protection for Doctors in Medical Practice Using Telemedicine According to Law Number 17 of 2023 Concerning Health - Fakhrurrozi Fakhrurrozi; Handar Subhandi Bakhtiar (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Health is a basic right guaranteed by the Indonesian constitution, as stipulated in Article 28H of the 1945 Constitution and Article 34 paragraph (3), which states that the state is responsible for the provision of adequate health care facilities for all citizens. Nonetheless, challenges in the provision of health services in remote areas are still significant, especially related to the limitations of facilities, medical personnel, and service quality. The development of technology, particularly telemedicine, has opened up new opportunities in the delivery of health services, which can overcome geographical limitations and improve community access to medical services. The type of research in this study is normative juridical. The research results in this discussion are the protection of doctors and the regulation of telemedicine policies in Indonesia, by reviewing Law Number 17 of 2023 concerning Health regarding the implementation of telemedicine between health service facilities. Although telemedicine can expand access to health, the risks associated with remote diagnosis and treatment require special attention in terms of legal protection of health workers. Therefore, adaptive legal tools are needed to accommodate the growing development of health technology and provide legal protection for the parties involved in the implementation of online-based health services.